1988
DOI: 10.1136/pgmj.64.750.322
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic spontaneous haemoperitoneum

Abstract: Summary:A case is described of bleeding arising from the falciform ligament which occurred in the absence of obvious local pathology. Spontaneous bleeding from this site hitherto has not.been reported. Previously described cases of idiopathic spontaneous haemoperitoneum and factors implicated in the aetiology of this rare condition are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…1 -3 It has been suggested that those patients younger than 45 years are likely to have congenital aneurysms of visreral arteries, whereas those older than 45 years are more likely to have less well-defined causes (but causes perhaps related to atherosclerosis and hypertension). 2 As of Sanderson's review in 1987,2 there had been only 51 reported cases of spontaneous peritoneal hemorrhage, with 38% of the cases without an identifiable bleeding point. 2 The male-to-female ratio was 3:2, with most cases occurring between ages 55 and 64 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 -3 It has been suggested that those patients younger than 45 years are likely to have congenital aneurysms of visreral arteries, whereas those older than 45 years are more likely to have less well-defined causes (but causes perhaps related to atherosclerosis and hypertension). 2 As of Sanderson's review in 1987,2 there had been only 51 reported cases of spontaneous peritoneal hemorrhage, with 38% of the cases without an identifiable bleeding point. 2 The male-to-female ratio was 3:2, with most cases occurring between ages 55 and 64 years.…”
Section: Discussionmentioning
confidence: 99%
“…2 As of Sanderson's review in 1987,2 there had been only 51 reported cases of spontaneous peritoneal hemorrhage, with 38% of the cases without an identifiable bleeding point. 2 The male-to-female ratio was 3:2, with most cases occurring between ages 55 and 64 years. The usual presentation is similar to that of our patient, with initially vague abdominal symptoms that progress to an acute abdomen, but cases have been described Management consists of maintaining a high index of suspicion and proceeding to laparotomy.l,2 Conservative management can be expected to produce a high mortality rate (up to 100% in one series),l.7 The diagnosis can be confirmed with diagnostic paracentesis; abdominal CT, plain x-ray films, and ultrasonography are less useful.l,7 Visceral angiography can be both diagnostic and therapeutic if a bleeding site can be localized.…”
Section: Discussionmentioning
confidence: 99%
“…[55][56][57][58] Portal hypertension seldom results in extraoesophaeal variceal haemorrhage but when bleeding is not into the gastrointestinal tract the diagnosis is difficult to make. Hepatocellular carcinoma is a common complication of cirrhosis and may present with intraperitoneal haemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…In the older age group. conservative management has been shown to have a virtual 100% mortality, whereas 70% of patients operated upon survived 18 . The management and prognosis for the younger age group is not defined, although laparotomy would seem mandatory.…”
Section: Discussionmentioning
confidence: 99%